Structural and dielectric properties of relaxor Sr0.5Ba 0.5Bi2Nb2O9 ceramic - Behera, B. [UNESP]; Araújo, E. B. [UNESP]; Júnior, A. F. (SAGE Publications, 2010)
Sr0.5Ba0.5Bi2Nb2O 9 ceramic was prepared by a conventional solid state reaction method and studied using X-ray powder diffraction and dielectric measurements. At room temperature, an orthorhombic structure was confirmed and their parameters were obtained using the Rietveld method. Dielectric properties were studied in a broad range of temperatures and frequencies. Typical relaxor behaviour was observed with strong dispersion of the complex relative dielectric permittivity. The temperature of the maximum dielectric constant Tm decreases with increasing frequency, and shifts towards higher temperature side. The activation energy Ea≈0·194±0·03 eV and freezing temperature Ta≈371±2 K values were found using the Vogel-Fulcher relationship. Conduction process in the material may be due to the hopping of charge carriers at low temperatures and small polarons and/or singly ionised oxygen vacancies at higher temperatures. © 2010 Maney Publishing.
Keywords: Aurivillius; Bismuth layered; Relaxor; Activation energy E; Conduction process; Dielectric constants; Dielectric measurements; Freezing temperatures; Higher temperatures; K-values; Low temperatures; Orthorhombic structures; Relative dielectric permittivity; Relaxor behaviour; Relaxors; Room temperature; Small polarons; Solid state reaction method; Strong dispersion; Vogel-Fulcher; Activation energy; Barium; Bismuth; Ceramic materials; Oxygen; Oxygen vacancies; Rietveld method; Solid state reactions; X ray powder diffraction; Permittivity